Circuits for Optical Based Line of Sight Voice Communication - Devasis Haldar; Shagun Panwar; Vipul Kumar; Ayush Goswami; Sakshi Dhawan (Institute of Advanced Engineering and Science, 2017)
We present here line of sight communication between a person and his neighbour with the help of optical signal produced by a laser torch which act as a carrier. It is therefore a wireless communication and the transmission can go up to 500 meters. We used photodiode to receive the signal at the receiver. The transmitter circuit comprises condenser microphone transistor amplifier BC547 followed by an op-amp stage built around µA741. When we give a voice signal from the mike, it converts the voice signal into the electrical signal. This electrical signal is fed to IC741 (op-amp) for amplification. The gain of the op-amp can be controlled with the help of 1-mega-ohm potentiometer. The AF output from IC is coupled to the base of a class B amplifier which, in turn, modulates the signal. The transmitter uses 5V power supply. However, the 3-volt laser torch (after removal of its battery) can be directly connected to the circuit-with the body of the torch connected to the class B. The photodiode converts the optical signal into electrical signal and again this signal is amplified using IC741 and a combination of class B push pull amplifiers. The receiver circuit uses an NPN photodiode as the light sensor that is followed by a two-stage transistor preamplifier and IC741 based audio Power amplifier. The receiver does not need any complicated alignment. Just keep the photodiode oriented towards the remote transmitter’s laser point and adjust the volume control for a clear sound. The sensor must not directly face the sun.